Clinical Evaluation of Kethoxal Against Cutaneous Herpes Simplex - Underwood, G. E. (1971)
A 2.5% preparation of kethoxal in cream was compared with the cream placebo for efficacy against cutaneous herpes simplex in a double-blind clinical study. The kethoxal formulation was not significantly more effective than the placebo. This conclusion was based on subjective impressions of the patients, observations by the physicians, and quantitative measurement of herpesvirus recovered from the lesions. It was suggested that the lack of clinical activity, in contrast to the marked activity against experimental infections in laboratory animals, resulted from the fact that high levels of herpesvirus were already present in the skin before symptoms were noted.